Kecukupan Keterbukaan Informasi Publik dalam Perspektif Tata Kelola Pelayanan e-KTP di Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Katingan - Sabirin Muhtar; Priadi Priadi (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2017)
This study aims to explain and describe the Sufficiency of Public Information Openness in the E-KTP Service Governance Perspective at the Katingan Regency Population and Civil Disablement Office. The type of research used is qualitative research methods, where data collection techniques are through observation, interviews, and documentation. Data analysis uses qualitative data analysis, namely data reduction, data presentation, and conclusion drawing. The primary data in this study as informants are in the Making of E-KTP (Head of Population Registration Services) in the Population and Registration Office of Katingan District, and Kepat Masyarakat of Katingan District and Secondary Sources, namely sources that do not directly provide data to data collectors, the data comes from materials, both in the form of books, articles, scientific works that are loaded in mass media such as magazines and newspapers, and scientific journals. Based on the results of the study using the theory of effectiveness related to the adequacy, it can be explained that the relevance of public information disclosure in the E-KTP Service Governance Perspective at the Katingan Regency Population and Civil Disability Service Office still has some need for improvement in providing Public Information Openness in the E-Service Governance perspective. KTP, about efficiency, adequacy, leveling, responsiveness, accuracy in providing public information disclosure to make E-KTP.